Recognition to the Customary Law of Indigenous Peoples in the ILO Convention 1989: Practices from Ecuador and Norway - Pratama, Kadek Wahyu Adi (UI Scholars Hub, 2019)
Recognition of the customary law of indigenous people is an integral part of the recognition to their existence as a whole. The 1989 ILO Convention concerning Indigenous and Tribal People in Independent Countries is an international instrument which obligates its parties to recognize indigenous people as well as its customary law. Ecuador and Norway are parties to the convention which will be used as examples for the implementation of the convention in recognizing respective indigenous people and laws. The indigenous people of both countries have similar history of struggles in obtaining the state’s recognition, and at the end they’re recognized through the constitution of their respective states. In the process of recognition, however, Ecuador and Norway have different but unique and typical characteristics with different results. These different characteristics and results are related to the different situations and conditions of the indigenous people and the political environment in Ecuador and Norway.